Functional and neurocognitive impairment in deficit schizophrenia patients in Peru and reliability of the bidimensional structure of negative symptomatology - Huarcaya Victoria, Jeff David (2024)
Many studies suggest that patients with deficit schizophrenia exhibit a more severe functional and neurocognitive impairment than those with non-deficit schizophrenia. However, there are few studies on this topic in Latin America. Objective: To examine the differences in functioning and neurocognitive impairment between patients with and without deficit schizophrenia, and to analyze the validity of the bifactorial structure of negative symptoms in a sample of Peruvian patients. Methods: A total of 53 Peruvian patients with schizophrenia were recruited. The Spanish version of the Schedule for the Deficit Syndrome (SDS) was used to diagnose the syndrome under study. The Functioning Assessment Short Test (FAST) was employed to assess global functioning, and the Screen for Cognitive Impairment in Psychiatry (SCIP), to evaluate neurocognitive functioning. Results: The prevalence of deficit schizophrenia was 62.3%. Patients with deficit schizophrenia exhibited greater impairment in working memory (p = 0.003), verbal fluency (p = 0.002), delayed verbal learning (p = 0.039), and processing speed (p = 0.004). Regarding global functioning, patients with deficit schizophrenia demonstrated poorer performance in the domains of autonomy (p = 0.002), occupational functioning (p = 0.001), cognitive functioning (p = 0.010), financial functioning (p = 0.015), interpersonal relationships (p < 0.001), and leisure time (p < 0.001). Conclusions: Patients with deficit schizophrenia display greater impairment in global and cognitive functioning. The replication of the bidimensional structure of negative symptoms in a Peruvian sample contributes to the hypothesis of the universality of the “expressive deficit” and “apathy-abulia” model.